Comparação de dois protocolos de exercícios físicos sobre capacidades físicas e cognitivas em idosos longevos: um estudo randomizado controlado - Ansai, Juliana Hotta (Universidade Federal de São Carlos, 2014)
Purpose: To compare the effect of 16-week multicomponent and resistance training and 6- week detraining protocols on cognition, depressive symptoms and physical variables related to falls in oldest-old people living in the community. Methods: We conducted a randomized controlled trial, with 69 community elderly over 80 years and without cognitive disorders. Participants were allocated to three groups (Control, Multicomponent and Resistance training). The Multicomponent Group performed a protocol consisting of warm-up, aerobic, strength, balance and cool-down exercises. The Resistance Group underwent strength exercises using six machines: leg press, chest press, calf, back extension, abdominal and rowing. The Control Group did not perform any intervention. The training sessions had progressive intensity, lasted 16 weeks and included three 1-hour sessions per week. We assessed the volunteers at baseline, at the end of 16-week training and after 6-week detraining. The assessment consisted of anamneses, Geriatric Depression Scale, cognition (Montreal cognitive assessment, clock drawing test, verbal fluency and gait associated to a cognitive task), lower limbs strength (sit-to-stand test), balance (unipedal and tandem tests), gait associated to a motor task and presence of falls. For statistical analysis, significance level of α=0.05 was adopted and the SPSS software was used (17.0). Results: There were no significant differences between groups and times in none of variables, when we analyzed by intention to treat. Regarding the detraining, there was a maintenance of physical and mental performances, without any difference between the groups. However, the adherence to training was low, mainly in the Multicomponent Group, which could have affected the results. Conclusion: Randomized controlled trials using adherence strategies, longer times and comparing variations of protocols are needed to verify which training protocols are more effective and consistent on cognition, depression and physical variables related to a higher risk of falls in oldest-old people.
Keywords: Fisioterapia; Idosos; Exercícios físicos; Cognição; Acidentes por quedas; Aged; 80 and over; Exercise; Cognition; Falls; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL